Safety and feasibility of high speed resistance training with and without balance exercises for knee osteoarthritis: A pilot randomised controlled trial - Pazit, L.; Jeremy, D.; Nancy, B.; Michael, B.; George, E.; Hill, Keith (Elsevier, 2018)
Objectives: People with knee osteoarthritis (OA) have increased risk of falling with impaired ability to rapidly respond and generate lower limb muscle power to arrest a fall. We examined the feasibility and safety of a high speed resistance training program with and without balance exercises. Design: A randomised controlled pilot trial comparing pre and post 8 weeks intervention within 3 groups: control, high speed resistance training (HSRT), high speed resistance training plus balance exercises (HSRTB). Setting: Exercise rehabilitation clinic. Participants: Twenty-eight participants (67.8 ± 6.5 yr) with knee OA. Main outcome measures: Feasibility and safety - adherence, drop-out rate, adverse events, pain during and post-exercise. Secondary measures - strength, mobility, functional tests, pain, executive function, satisfaction. Results: High adherence (99.3% HRST, 96.8% HRSTB), high satisfaction (92% HRST, 91% HRSTB), no drop-outs or serious adverse events, and reduced overall pain were reported. Almost 1 in 5 sessions resulted in substantial pain incidents, although these typically settled quickly. Significant improvements occurred in function, strength and mobility following the 8 weeks for intervention groups. Conclusion: Both exercise groups were feasible and safe and improved physical function and strength. Further study is required to examine the optimal combination of high speed resistance and balance exercises and its effect on falls in people with knee OA.